A fascinating case of complex congenital heart disease - Divvela, Soumya; Jensy Jaison; Rajoo Ramachandran (Asian Journal of Medical Sciences, 2024)
Complex congenital heart disease (CHD) constitutes a significant non-infectious contributor to childhood morbidity and mortality, particularly prevalent in developing countries with an estimated incidence of nearly 1/100 births. The spectrum of CHD spans from isolated atrial septal defects that necessitate no immediate intervention to intricate structural cardiovascular abnormalities demanding multiple interventions early in the neonatal period. Patients afflicted with complex CHD often manifest symptoms such as respiratory distress, cyanosis of the skin, feeding difficulties, and failure to thrive, becoming evident within the initial 48 h post-birth. In this context, we present an intriguing case of a male child with complex CHD. This case study is accompanied by a concise exploration of the embryology of the heart, shedding light on the intricate developmental processes that may underlie such congenital anomalies.